Single Cell RNA-Sequencing Reveals a Murine Gallbladder Cell Transcriptome Atlas During the Process of Cholesterol Gallstone Formation - Liang, Jingjia; Shao, Wentao; Liu, Qian; Lu, Qifan; Gu, Aihua; Jiang, Zhaoyan (Frontiers in Cell and Developmental Biology, 2021)
Gallstone disease is a worldwide common disease. However, the knowledges concerning the gallbladder in the pathogenesis of cholesterol gallstone formation remains limited. In this study, using single-cell RNA sequencing (scRNA-seq), we showed cellular heterogeneity and transcriptomic dynamics in murine gallbladder cells during the process of lithogenesis. Our results indicated gallbladder wall were subjected to remodeling during the process of lithogenesis. The major molecular events happened included proliferation of epithelial cells, infiltration of immune-cells, activation of angionesis and extracellular matrix modulation. Furthermore, we observed partial reversal of gallbladder cell transcriptomes by ursodeoxycholic acid treatment. This work thus provides novel and integral knowledges on the cellular changes during lithogenesis, which is of great significance to the understanding of pathogenesis and treatment of cholesterol gallstone.